(untitled) (Fiep Bulletin - online, 2014)
The present study had as its main goal to verify whether the patterns of corporal compotion enaluation for adults do have a correlation to the sample reality within the municipal district of Cornélio Procópio, northern Paraná, Brazil. The sample had the support of physically active women belonging to the Third Age period. It was realized stature and weight testes as well as waist circumference and the protocol of Functional autonomy of the Group of development for Latim Americam Maturity (GDLAM). The data were submitted to the correlation analysis in order to understand and conclude the study. After the analysis, the results pointed out that the ideal patterns established for adults are not in consonance to the third age women´s lifestyle.